Crawl Stroke Teaching Aid #1. - Rushall, B. S.
This collage of sequences from some of the world's best crawl strokers (males and females) is presented as a teaching aid in Dr. Rushall's Stroke Clinics. Each item is presented to show important features of the stroke that should be adapted to each individual's capabilities. The sequences are from Grant Hackett, Claudia Poll, Alexandre Popow and janet Evans.